The Paradox of Resource Nationalism and the Human Security Crisis: Study of the PT Freeport Indonesia Conflict Post Majority Share Acquisition (2017 – 2025) - Nibal, Rachel Kamilia Faradiba; Phoenna, Riezky Poetra; Novia, Hana; Elindawati, Rifki (SIYAR Journal, 2026)
Indonesia’s majority share acquisition in PT Freeport Indonesia (PTFI) since 2017 is often narrated as a success of resource nationalism, yet human security conditions for indigenous Papuan communities around the mining area remain precarious. Drawing on the human security framework (UNDP) and the concept of structural violence (Galtung), and applying Fairclough’s critical discourse analysis to corporate communications, official statements, policy documents, and human rights reporting from 2017–2025, this study explains why ownership change has not translated into local protection. The analysis shows how the paired discourse of “sovereignty”, “development”, and “security” reframes labor conflict and coercive governance as necessary for stability and investment, thereby normalizing exclusion. Empirically, the crisis is manifested in the 2017 strike-related dismissals and subsequent terminations affecting approximately 8,000–8,300 workers, restrictions on access to housing and essential services (including health care and schooling), and persistent environmental violations documented by state authorities. These dynamics generate interconnected threats to economic, health, environmental, and community security, producing haram through institutional arrangements rather than isolated incidents. While Papuan workers and customary institutions mobilize resilience through strikes, litigation, and advocacy, their claims remain politically unresolved. The article concludes that resource nationalism is insufficient unless it is accompanied by rights-based governance that de-securitizes Papua’s policy space and makes corporate accountability meaningful at the local level